PERSEPSI MAHASISWA (NON – ENGLISH) TENTANG KEBIJAKAN TOEFL SEBAGAI SYARAT KELULUSAN - Arina Hafadhotul Husna (Badan Penerbit STIEPARI Press, 2022)
To realize the vision, mission, and goals of the institution, The Institute Technology & Health Cendekia Utama Kudus compiles and formulates standards that regulate excellent graduate competency. One additional performance indicator in the standard graduate competency of education standard states that students are required to have a minimum Test of English as Foreign Language (TOEFL) score of 450. TOEFL is a standardized test of English as a foreign language used to test a student's ability in mastering English. This study aims to determine student perceptions of the TOEFL policy as a graduation requirement, as well as observe the challenges & difficulties faced by the students in the implementation. This research is a descriptive qualitative study. Respondents were final semester students in the study program at ITEKES Cendekia Utama Kudus. A questionnaire with a Likert scale of 1-5 was used as an instrument in this study. The results of this study indicate that students' perceptions of this policy are very positive. Students become more aware of the importance of English and have high motivation to graduate on time. Positive perceptions are also shown in the English course because it helps them to pass the TOEFL, and increases students’ motivation in learning English. Some students also consider the TOEFL score set is very high, the time required for preparation is very short, the test fee is expensive, and the policy set is too difficult, but the majority of students have a neutral response and can implement this policy well. The difficulties and challenges that most students face in the TOEFL are time allocation, lack of preparation, and lack of mastery of English grammar. Therefore, the institution must prepare and provide good facilities so that students can meet and exceed the specified passing grade maximally. Intensive TOEFL courses should be given to reduce the difficulties faced by students.